Integrated lens antenna array with full azimuth plane beam scanning capability at 60 GHz. Issue 1 (January 2017) - Saleem, Muhammad Kamran; Alkanhal, Majeed A. S.; Sheta, Abdel Fattah; Abdel‐Rahman, M.; Himdi, Mohammed
ABSTRACT: An antenna array operating at 60 GHz is proposed. The proposed array covers impedance bandwidth of 5 GHz (57.5–62.5 GHz) with maximum gain of 16.25 dBi at 61. 5 GHz. With the proposed array 15 distinct radiation patterns in azimuth plane can be achieved, each having 3‐dB beamwidth of 24° and 3‐dB cross over. The beam scanning capability can be achieved by activating each array element one by one. Each array element consists of a conventional microstrip patch antenna (MPA) integrated with extended hemispherical Teflon lens. The Teflon lens is utilized to enhance the gain of conventional MPA as well as to achieve the desired elementary radiation pattern of array to cover full azimuth plane. A very good agreement between the measured and simulated results is observed. © 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 59:116–120, 2017